Inclusion of a Termination of Coverage Clause in an Insurance Policy Issued by PT Asuransi Artarindo - Andieni Diva Aprilita; Eny Sulistyowati (NOVUM : JURNAL HUKUM, 2025)
The inclusion of a coverage termination clause in insurance policies is mandated under Article 11 letter k of OJK Regulation Number 23/POJK.05/2015 concerning Insurance Products and Marketing. However, the same clause is restricted under Article 30 paragraphs (4) and (5) of OJK Regulation Number 6/POJK.07/2022, which prohibits exculpatory clauses that limit insurers' responsibilities. This study aims to analyze the validity of the coverage termination clause in Article 7 of PT Asuransi Artarindo’s Insurance Policy in relation to the prohibition of exculpatory clauses and to examine its legal consequences. This research is normative legal research, utilizing a statutory and conceptual approach. Data is collected through literature study and analyzed prescriptively. The findings indicate that the termination clause in PT Asuransi Artarindo’s policy aligns with Article 11 letter k of OJK Regulation 23/POJK.05/2015 and with Articles 249, 276, and 293 of the Indonesian Commercial Code. The clause does not meet the criteria of an exculpatory clause as defined in Article 30 of OJK Regulation 6/POJK.07/2022. Consequently, the legal impact of its inclusion is minimal, as the agreement fulfills both subjective requirements (mutual consent and legal capacity) and objective requirements (legal cause and lawful object). Therefore, the policy remains valid and enforceable. This study recommends clearer regulatory harmonization between OJK regulations to avoid legal ambiguity for insurers and consumers in the future.